Determinants of commercial bank credit risk in Malaysia/ Nurfarah Diana Ahmad Supian - Ahmad Supian, Nurfarah Diana (2018)
Credit risk is an important issue that can affects the failure of banks. Bank offering loan to borrowers as to maximizing profit and increase their assets. Bank has high probability to face credit risk when borrowers fail to pay back the loan. Most of the past researcher used non-performing loan to measure credit risk. So, this study is conducted to determinants of credit risk which solely focuses on the commercial bank in Malaysia. The study comprises a sample of 27 of commercial bank credit risk that are analysed over the period of 2015 to 2017 by employing descriptive, correlation and multiple linear regression.. The study used Return on Asset (ROA), Total Loan to Total Asset (TLTA) and Inflation (INF)) as independent variables to test the relationship with dependent variable which is credit risk. The data of the study is obtained from report of the bank, national bank report, world data bank and data stream. The study found out that Return on Assets (ROA) has negative and significant towards credit risk while TLTA and INF are not significant with credit risk.